Taeniasis: symptoms, diagnosis and treatment – a systematic review - Napieralska, Agnieszka; Garbarczyk, Wiktor; Kapla, Albert; Černohorská, Alicja; Bednarczyk, Daria; Białeta, Julia; Siembab, Karolina; Rowińska, Katarzyna; Jurkiewicz, Michalina; Pysiewicz, Wiktoria (Journal of Education, Health and Sport, 2025)
Human taeniasis is caused by infection with one of three Taenia species: Taenia saginata, Taenia solium, and Taenia asiatica. It is a parasitic disease that remains a public health concern in endemic regions. This systematic review examines the clinical manifestations, diagnostic approaches, and methods of treatment for taeniasis. A comprehensive analysis of available literature highlights the diverse symptomatology, ranging from asymptomatic carriers to individuals with life-threatening complications. Advances in diagnostic techniques, including molecular methods, have improved detection rates, while pharmacological treatments like praziquantel and niclosamide remain the key elements of therapy. This review underscores the importance of integrated control strategies to reduce the burden of taeniasis, including sanitation improvements and public health education.